2019
DOI: 10.1002/jgh3.12246
|View full text |Cite
|
Sign up to set email alerts
|

Additional effect of magnifying narrow‐band imaging on estimating the invasion depth of superficial esophageal cancer

Abstract: Background and Aim To investigate whether assessment by magnifying narrow‐band imaging (M‐NBI) based on the classification of the Japan Esophageal Society provides additional value to the estimation of the invasion depth of superficial esophageal squamous cell carcinoma (SCC) compared with assessment by white light endoscopy (WLE) alone. Methods Endoscopic images of 211 consecutive superficial esophageal SCCs resected by endoscopic submucosal dissection were separated into WLE and M‐NBI images. Depth estimatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, there can be considerable discrepancy between clinical and pathological diagnoses, especially MM/SM1 cancers, because the accuracy of endoscopic diagnosis of pathological MM/SM1 is relatively poor [ 9 , 21 ]. Kato et al reported diagnostic accuracies of 71% and 65% for superficial ESCC depth assessed by WLE alone and WLE with M-NBI endoscopy, respectively [ 7 ], while Wang et al reported diagnostic accuracies of 53% and 57%, respectively, using the same two methods [ 8 ]. These studies emphasize the urgent need to identify biomarkers for superficial ESCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there can be considerable discrepancy between clinical and pathological diagnoses, especially MM/SM1 cancers, because the accuracy of endoscopic diagnosis of pathological MM/SM1 is relatively poor [ 9 , 21 ]. Kato et al reported diagnostic accuracies of 71% and 65% for superficial ESCC depth assessed by WLE alone and WLE with M-NBI endoscopy, respectively [ 7 ], while Wang et al reported diagnostic accuracies of 53% and 57%, respectively, using the same two methods [ 8 ]. These studies emphasize the urgent need to identify biomarkers for superficial ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of precancerous and superficial ESCC remains challenging for endoscopists because the lesions are easily overlooked by conventional white light endoscopy (WLE); indeed, about 40% of lesions are thought to be missed [ 5 ]. WLE endoscopy together with magnifying narrow-band imaging (M-NBI) has thus become the standard method for the detection of superficial ESCC [ 6 , 7 ]. Even so, the invasion depth of ESCC is difficult to determine accurately and intraobserver and interobserver variation are common.…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines have different positions on the use of AEI. Since the publication of the previous ESGE priorities, 17 studies examining NBI, blue-light imaging (BLI), i-scan, and chromoendoscopy with acetic acid and Lugol's iodine have been published and were analyzed, of which nine were prospective and eight retrospective [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. An additional 19 studies were found on less common techniques including endomicroscopy and the application of computer-assisted diagnosis.…”
Section: When Can Anticoagulant Medication Be Restarted Following Gastrointestinal Bleeding?mentioning
confidence: 99%